Climate change and sovereign risk: A regional analysis for the Caribbean - Matthew Agarwala; Matt Burke; Jennifer Doherty-Bigara; Patrycja Klusak; Kamiar Mohaddes (Inter-American Development Bank (IDB), 2024)
Climate change is an existential threat to the world economy, with complex, evolving and nonlinear dynamics that remain a source of great uncertainty. There is a bourgeoning literature on the economic impact of climate change, but research on how climate change affects sovereign risks is limited. This paper provides forward-looking regional analysis of the effects of climate change on sovereign creditworthiness, probability of default and the cost of borrowing for the Caribbean economies. Our results indicate that there is substantial variation in the sensitivity of ratings to climate change across the region which is due to the non-linear nature of ratings. Our findings improve the identification and management of sovereign climate risk and provides a forward-looking assessment of how climate change could affect the cost of accessing international finance. As such, it leads to a suite of policy options for countries in the region.
Keywords: C33; C53; G10; G18; H63; O44; O54; Q51; Q54; 330; Sovereign credit rating; climate change; counterfactual analysis; climateeconomy models; sovereign debt; physical risks; fiscal policy; transition risks; Latin America; Caribbean